2009
DOI: 10.1177/104063870902100615
|View full text |Cite
|
Sign up to set email alerts
|

Isolation Rates, Serovars, and Toxin Genotypes of Nicotinamide Adenine Dinucleotide-Independent Actinobacillus Pleuropneumoniae among Pigs Suffering from Pleuropneumonia in Spain

Abstract: Abstract. Actinobacillus pleuropneumoniae is the etiologic agent of swine pleuropneumonia, a major production-limiting disease in the pig industry. In the current study, 2,171 lung specimens obtained from pigs housed in 870 Spanish pig farms in regions of substantial pig production were examined. Conventional microbiology, coupled with species-specific polymerase chain reaction, identified 127 biovar 2 isolates, accounting for 25.3% of all A. pleuropneumoniae (n 5 502) detected. Most isolates (79%) were recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 14 publications
(45 reference statements)
3
21
0
Order By: Relevance
“…Normally, serovars 1-12 and 15-16 are biovar 1, and serovars 13 and 14 are biovar 2. However, some biovar 2 isolates belonging to serovars other than 13 and 14(Beck et al, 1994;Dom & Haesebrouck, 1992;Maldonado, Valls, Mart ınez, & Riera, 2009), as well as a biovar 1 serovar 13 isolate(Perry et al, 2012), have been identified. Additionally, some untypable isolates have been reported(Ito, Ogawa, Fukamizu, Morinaga, & Kusumoto, 2016;Kokotovic & Angen, 2007).…”
mentioning
confidence: 99%
“…Normally, serovars 1-12 and 15-16 are biovar 1, and serovars 13 and 14 are biovar 2. However, some biovar 2 isolates belonging to serovars other than 13 and 14(Beck et al, 1994;Dom & Haesebrouck, 1992;Maldonado, Valls, Mart ınez, & Riera, 2009), as well as a biovar 1 serovar 13 isolate(Perry et al, 2012), have been identified. Additionally, some untypable isolates have been reported(Ito, Ogawa, Fukamizu, Morinaga, & Kusumoto, 2016;Kokotovic & Angen, 2007).…”
mentioning
confidence: 99%
“…Serotype 2 strains of A. pleuropneumoniae, which are dominant in Europe, produce two different exotoxins, while serotype 2 strains isolated in North America and Canada produce only one toxin (Gottschalk, 2012). Serotypes 2, 4 and 7 are the most common in Spain (Maldonado et al, 2009) and serotype 2 is the most frequent in Switzerland (Stärk et al, 2007). Serotypes 2, 3, 6-8, 10, 12 and 9 was reported to be dominant in the United Kingdom (Bossé et al, 2014), while serovar 15 was the leading type in Australia (Blackall et al, 2002).…”
mentioning
confidence: 99%
“…Serotypes 5, 7, 8 were the most frequently isolated types in Canada (Gottschalk and Lacouture, 2015). Biotype II strains are more commonly isolated in Europe, e. g. in Hungary (Fodor et al, 1989), in Denmark (Nielsen et al, 1997) and in Spain (Maldonado et al, 2009) than in the US (Perry et al, 2011).…”
mentioning
confidence: 99%
“…This highly contagious respiratory disease is widely spread among pig-keeping countries causing major economic losses in the swine industry (21,30). The most important A. pleuropneumoniae virulence factors include surface polysaccharides (18), iron uptake systems (4), Apx toxins (11,16,28), components of anaerobic metabolism (17), and outer membrane proteins (8,12).…”
Section: Praca Oryginalnamentioning
confidence: 99%
“…On the basis of the β-nicotinamide adenine dinucleotide (β-NAD) requirement for growth A. pleuropneumoniae has been classified into biovar 1 (β-NAD dependent) and biovar 2 (β-NAD independent). Biovar 2 can synthesize NAD in the presence of specific pyridine nucleotides or their precursors (6,21). Each biovar is further divided into serovars.…”
Section: Praca Oryginalnamentioning
confidence: 99%